2018
DOI: 10.5005/jp-journals-10018-1259
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma in Malaysia and Its Changing Trend

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of death globally. In Malaysia liver cancer is the eighth most common cause of cancer for both gender and fifth most common cause of cancer for males. Liver cancer is a cause of premature death in Malaysia: The trend from 1990 to 2010 was observed upward. Since 1990, the annual years of life lost (YLLs) from liver cancer have increased by 31.5%. Older persons are at higher risk and there is male predominance observed. Curative surgical resection, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…According to a previous study, the main causes of HCC among Indians are alcohol-related and cryptogenic. Meanwhile, viral hepatitis B infection was the leading cause of HCC among Malay and Chinese people [ 6 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, the main causes of HCC among Indians are alcohol-related and cryptogenic. Meanwhile, viral hepatitis B infection was the leading cause of HCC among Malay and Chinese people [ 6 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotype C along with genotype D carries a higher risk for developing cirrhosis and HCC. 31 Thus, it is expected that the demand for liver transplantation will increase. Also, studies have shown that the incidence of end-stage liver disease secondary to HCV is projected to rise, 32 increasing the burden of end stage liver disease furthermore.…”
Section: Barriers To Liver Transplantationmentioning
confidence: 99%
“…HBV is the most predominant etiology of hepatocellular carcinoma and liver cirrhosis in Malaysia [ 6 , 7 ]. HBV infection attributed to 51.3% of all hepatocellular carcinoma cases in Malaysia, whereas the incidence of cryptogenic cases having doubled within 10 years accounted for 35.7% of local hepatocellular carcinoma cases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%